Analysis and Calculation of PPH Article 21 For Permanent Employees on Regular and Unregular Income - Affanza Favernanda Akhlaqul Abrar; Hengky Reynaldi Chan; Galuh Tresna Murti; Sultan Hanif Wibisono (Universitas Muhammadiyah Makassar, 2023)
Employees are people who have provided services in the form of labor or work for which they will be paid according to the services they have provided to the Institution. Payments received by employees in the form of salaries given per certain period, these salaries will later be subject to tax which will be calculated as the employee's contribution to the state. Based on PPh article 21, taxes taken from income in the form of income tax are types of taxes taken based on salaries, wages and other payments received by employees.